Parasitic skin infections: neglected diseases or just challenging for diagnosis? - Gardini, Giulia; Tomasoni, Lina Rachele; Castelli, Francesco (Current opinion in infectious diseases, 2020)
The aim of the article is to review the most recent evidence concerning parasitic skin infections. Parasitic skin infections are increasingly reported worldwide. Special at-risk categories are migrants, returning travelers, and immunocompromised individuals, who are at higher risk to present disseminated disease. The number of reported cases is growing even outside the endemic areas as a consequence of international travels, migration flows, increasing immunocompromised population, climate change, and natural disasters. Skin parasitoses are neglected infections. Funding assigned to prevent and treat them is limited, even if they affect millions of persons worldwide. Diagnosis could be a challenge for clinicians of high-income countries who are facing an increasing number of such infections related to great epidemiological events.